Estrutura de propriedade e teoria da agência: um estudo de empresas brasileiras e seus diferentes tipos de controladores - Balassiano, Marcel Grillo (2012)
The structure of anglo-saxon ownership, and its classical agency problem, with conflicts between manager and shareholders, characterized by pulverized properties, although prevalent in literature, does not establish the rule, but the exception. Differently from United States and England, Brazil has a concentrated ownership structure, where the influence of major shareholders is strong. In this case, conflict is not between manager and shareholders (principal - agent conflict), but between major shareholders and minor shareholders (principal - principal conflict). In the brazilian capital market, there are two types of stock – ordinary (voting stock) and preferential (non voting stock). This breaks the current rule in many countries - like United States – in which one stock means one vote. Thus, in many cases, there is a combination of too much power with very few resource allocation in the company. That said, it is the object of the present study to find an estimate of magnitude related to voting stocks, cash flow and the excess of vote by major shareholders, of companies listed in the Ibovespa - Bovespa Index, in the years of 2009-2010 (theoretical portfolio of the third period of four months of said years), segregating them by acting sector and type of major shareholder. For this study, a sample of 121 companies was analysed, using methodologies for the ends (descriptive and explanatory) and for the means (bibliographic and documental). Data collection was obtained using the ―Economática‖ System and the ―IAN‘s‖ of the brazilian ―Comissão de Valores Mobiliários (CVM)‖. As a result, this research confirmed the hypothesis of the current literature, which states that the open capital of the brazilian companies is concentrated, especially the stock capital (51,95% mean and 51,20% median in 2009, and 47,16% mean and 51,70% median in 2010), with the occurrence of a significant distance between the power of voting and the power of the cash flow of major shareholders (1,10 mean and 1,24 median in 2009, and 1,07 mean and 0,98 median in 2010). With this study, it is also possible to conclude that the principal - principal conflict is predominant in Brazil.